Synthesis and in vitro evaluation of fluorine-18 benzimidazole sulfones as CB2 PET-radioligands. Issue 20 (9th May 2019) - Kallinen, Annukka; Boyd, Rochelle; Lane, Samuel; Bhalla, Rajiv; Mardon, Karine; Stimson, Damion H. R.; Werry, Eryn L.; Fulton, Roger; Connor, Mark; Kassiou, Michael
Abstract : New 18 F-fluorinated benzimidazole 5-sulfones with low nanomolar binding affinity were synthesised as PET-radioligand candidates for the CB2 receptor. Abstract : Cannabinoid type 2 receptor (CB2) is up-regulated on activated microglial cells and can potentially be used as a biomarker for PET-imaging of neuroinflammation. In this study the synthesis and pharmacological evaluation of novel fluorinated pyridyl and ethyl sulfone analogues of 2-( tert -butyl)-5-((2-fluoropyridin-4-yl)sulfonyl)-1-(2-methylpentyl)-1 H -benzo[ d ]imidazole ( rac -1a ) are described. In general, the ligands showed low nanomolar potency (CB2 EC50 < 10 nM) and excellent selectivity over the CB1 subtype (>10 000×). Selected ligands1d, 1e, 1g and3l showing high CB2 binding affinity ( K i < 10 nM) were radiolabelled with fluorine-18 from chloropyridyl and alkyl tosylate precursors with good to high isolated radioactive yields (25–44%, non-decay corrected, at the end of synthesis). CB2-specific binding of the radioligand candidates[ 18 F]- 1d and[ 18 F]- 3l was assessed on rat spleen cryosections using in vitro autoradiography. The results warrant further in vivo evaluation of the tracer candidates as prospective CB2 PET-imaging agents.